Analisis Fenomena Postpartum Depression dalam Perspektif Al-Qur’an : Studi Tentang Pola Asuh - Iffah; Iffah Najmi Maryam (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Postpartum depression is a continuation of the condition experienced by mothers after childbirth, commonly known as baby blues. Baby blues are common among postpartum mothers due to a sharp decline in hormones, leading to significant emotional or mood changes felt by the mother. It is mentioned in the Qur'an, in Surah Al-Baqarah verse 233, the command to pay more attention to mothers after childbirth, as this period is very fragile for a mother, considering the immense struggle and risk to her life during childbirth. The verse states,